(3ZPGA GdCdHGH dTQM efXheI GdBOGHs - (3GdSaGQjfi CHi GdYhf eMeO Hf CMeOs; (3TeS GdOjf CHh YHO Gddg eMeO Hf YHO Gdbhj GdeQOGhj GdfMhj GdMfHdjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg GdHjGf CeG HYO abO cGf SCdfi HYV GdENhGf Cf CTQM efXheI GdBOGH fXe TeS GdOjf CHh YHO Gddg GdeQOGhi TQMkG jMd eHGfjgG hjXgQ eYGfjgG s
(3BNQgG (B:s
(3eKd MGdgf HMGed NQL Ydi cJag CMO TbJjg cdeG fXQJ QCJgG hgPg MGd LejY GddDeGA jMaXhf GdSjFGJ Efg Ydi cd TF bOjQ hHGdELGHI LOjQ Bejf s
(3GdeNWhW eWHhY HeWHYI GdfLGM HeUQ GdeMQhSI dUGMHgG eMeO MSjf GdJQRi SfI (B1324(3g`s
(3eQbe GdUaMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs